2012
DOI: 10.1111/j.1471-4159.2012.07704.x
|View full text |Cite
|
Sign up to set email alerts
|

Kv7 (KCNQ) channel openers normalize central 2‐deoxyglucose uptake in a mouse model of mania and increase prefrontal cortical and hippocampal serine‐9 phosphorylation levels of GSK3β

Abstract: J. Neurochem. (2012) 121, 373–382. Abstract Several metabolic neuroimaging studies have indicated that bipolar patients with mania exhibit alterations in metabolic activity, suggesting that perturbations in corticolimbic function contribute to the functional deficits associated with the disease. Because pharmacological stimulation of Kv7 channel function has shown anti‐manic like efficacy in the D‐amphetamine and chlordiazepoxide (AMPH+CDP) induced hyperactivity mouse model of mania, we addressed whether this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
(108 reference statements)
0
16
0
Order By: Relevance
“…Inhibition of the hippocampal M-current has been proposed as a general strategy to improve cognitive performance ( Fontan-Lozano et al, 2011); on the other hand M-current openers in prefrontal cortex and hippocampus resulted helpful in mouse model of BPD and schizophrenia. These pre-clinical data indicate that M-current activation restores several key signaling pathways in psychosis similarly to standard drugs, like lithium and valproate ( Kristensen et al, 2012). Kir channels are molecular targets of several antidepressants, thus suggesting that these channels may contribute to the therapeutic action (or adverse effect) of these drugs ( Ohno et al, 2007; Furutani et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Inhibition of the hippocampal M-current has been proposed as a general strategy to improve cognitive performance ( Fontan-Lozano et al, 2011); on the other hand M-current openers in prefrontal cortex and hippocampus resulted helpful in mouse model of BPD and schizophrenia. These pre-clinical data indicate that M-current activation restores several key signaling pathways in psychosis similarly to standard drugs, like lithium and valproate ( Kristensen et al, 2012). Kir channels are molecular targets of several antidepressants, thus suggesting that these channels may contribute to the therapeutic action (or adverse effect) of these drugs ( Ohno et al, 2007; Furutani et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
“…Potassium channels have been proposed to play a role in mechanisms of neural plasticity which are altered in various psychiatric disorders, especially in hippocampus ( Askland, 2006; Fontan-Lozano et al, 2011; Shah et al, 2011; Kristensen et al, 2012). Multiple linkage and association studies have suggested chromosome 8q24 as a promising candidate region for BPD ( Park et al, 2004; Zandi et al, 2008).…”
Section: Neuropsychiatric Disorders Associated To Ion Channels Dysfunmentioning
confidence: 99%
See 1 more Smart Citation
“…It also inhibits GSK3β which is responsible for the phosphorylation of Kv7.2/Kv7.3, and phosphorylation of these channels suppresses the M-currents to promote neuronal hyperexcitability (Borsotto et al, 2007). Interestingly, ezogabine, which is a recently approved antiepileptic drug (AED) that targets Kv7.2/Kv7.3 channels, has been shown to have mood stabilizing properties in animal models (Dencker et al, 2008; Redrobe and Nielsen, 2009; Dencker and Husum, 2010; Kristensen et al, 2012) and in a small pilot study in humans (Amann et al, 2006). Finally, a previous genetic study found evidence of an association between variants in KCNQ2 and BP (Borsotto et al, 2007), and our group has reported genome-wide significant linkage of BP with chromosome 8q24 in a region that harbors KCNQ3 (Avramopoulos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One study (Redrobe and Nielsen, 2009) used a mouse model of mania and determined that EZG (a non-selective opener) and ICA-27243 (a selective Kv7.2/3 opener), but not BMS-204352 (a selective Kv7.4–Kv7.5 and Kv7.7/3 heteromer opener) were able to reduce motility in the hyperactive mice, a paradigm for antimanic properties in drugs. In another study employing the D -amphetamine and chlordiazepoxide (AMPH + CDP) mouse model (Kristensen et al, 2012), EZG reduced cerebral glucose metabolic activity while increasing phosphor-serine-9 levels of GSK3β with a brain regional signature that mirrored lithium and valproate.…”
Section: Ion Channels As Therapeutic Targetsmentioning
confidence: 99%